Evaluation of Essential Medicine Availability to Support Integrated Primary Health Care in Batang Hari District Primary Health Centers - Susy Mardianti; Dwi Noerjoedianto; Herwansyah Herwansyah; Asparian Asparian; Muldiasman Muldiasman; Willia Novita Eka Rini (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Adequate availability of essential medicines is a critical component in ensuring the continuity of Integrated Primary Health Care (IPC) services. Objective: This study aimed to evaluate the availability of essential medicines in supporting IPC implementation at Primary Health Centers in Batang Hari Regency. Methods: A qualitative descriptive study was conducted using in-depth interviews, observations, and document reviews. Informants were selected through purposive sampling, comprising heads of primary health centers, drug managers, IPC coordinators, and District Health Office representatives. Data were analyzed thematically using an input–process–output evaluation framework. Results and Discussion: Of 40 essential medicine types observed, 16 (40%) were sufficiently available across all health centers, 13 (32.5%) were available but limited in several facilities, 7 (17.5%) experienced stock-outs in some health centers, and 4 (10%) were entirely unavailable across all studied facilities. Stock-outs persisted from several weeks to months, driven by distribution delays, supply-demand mismatches, and inadequate stock monitoring systems, resulting in increased patient referrals and out-of-pocket medicine purchases. Conclusions: The availability of essential medicines has not yet fully supported optimal IPC implementation. Strengthening demand planning, improving logistics distribution timeliness, and enhancing coordination between primary health centers and the district health office are essential to ensure sustainable medicine availability in support of comprehensive primary health services